2013
DOI: 10.1182/blood-2012-08-446096
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of PI3K-related DNA damage response kinases and mTORC1 induces apoptosis in MYC-driven B-cell lymphomas

Abstract: Key Points• MYC-driven lymphomas demonstrate activation of mTORC1 and an endogenous DNA damage response.• BEZ235 inhibits PI3K-related DNA damage response kinases and mTORC1, inducing p53-independent upregulation of proapoptotic BMF.Pharmacological strategies capable of directly targeting MYC are elusive. Previous studies have shown that MYC-driven lymphomagenesis is associated with mammalian target of rapamycin (mTOR) activation and a MYC-evoked DNA damage response (DDR) transduced by phosphatidylinositol-3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…PI3K-AKT-mTOR signaling modulates mRNA translation at both the initiation and elongation stages, including the promotion of eIF4E-dependent 5′ CAP-dependent translation initiation (20,21,23,25,26). We and others have previously demonstrated the vulnerability of MYC-driven B-lymphoma cells to a number of targeted therapeutic strategies that inhibit PI3K-AKT-mTOR signaling (18,20,(27)(28)(29)(30)(31). However, in all cases, disease relapse occurred despite continuing single-agent therapy.…”
Section: Research Briefmentioning
confidence: 99%
See 2 more Smart Citations
“…PI3K-AKT-mTOR signaling modulates mRNA translation at both the initiation and elongation stages, including the promotion of eIF4E-dependent 5′ CAP-dependent translation initiation (20,21,23,25,26). We and others have previously demonstrated the vulnerability of MYC-driven B-lymphoma cells to a number of targeted therapeutic strategies that inhibit PI3K-AKT-mTOR signaling (18,20,(27)(28)(29)(30)(31). However, in all cases, disease relapse occurred despite continuing single-agent therapy.…”
Section: Research Briefmentioning
confidence: 99%
“…38), including the proapoptotic BH3-only protein BCL2 modifying factor (BMF; refs. 29,39). In response to AKTi-1/2, KU-63794, BEZ235, and everolimus treatment, a robust increase in BMF protein abundance was detected in Eμ-Myc lymphoma cells (Fig.…”
Section: Pi3k-akt-mtor Inhibitor-but Not Cx-5461-mediated B-lymphoma mentioning
confidence: 99%
See 1 more Smart Citation
“…113,[136][137][138] The mechanism that explains this observation is related to the ability of MTORC1 to regulate the expression of FAN1/FANCD2, a protein involved in the activation of ATM. Thus, the inhibition of MTORC1 decreases FAN1, which impairs the activation of ATM and thereby the DDR of cancer cells.…”
Section: Targeting Glutaminolysis and Autophagy As An Anticancer Therapymentioning
confidence: 99%
“…Oral NVP-BEZ235 is reported to inhibit the kinase activities of mTORC1, mTORC2 and PI3K (15). Several pre-clinical studies reported the efficacy of NVP-BEZ235 in various lymphoid malignancies (14,(16)(17)(18) and its effects, either alone or in combination with other compounds, are currently being tested in the treatment of various other malignancies (12).…”
Section: Introductionmentioning
confidence: 99%